Crosstalk Between Hypoxia and ER Stress Response: A Key Regulator of Macrophage Polarization - Díaz-Bulnes, Paula; Saiz, María Laura; López-Larrea, Carlos; Rodríguez, Ramón M. (Frontiers in Immunology, 2020)
Macrophage activation and polarization are closely linked with metabolic rewiring, which is required to sustain their biological functions. These metabolic alterations allow the macrophages to adapt to the microenvironment changes associated with inflammation or tissue damage (hypoxia, nutrient imbalance, oxidative stress, etc.) and to fulfil their highly energy-demanding proinflammatory and anti-microbial functions. This response is integrated via metabolic sensors that coordinate these metabolic fluxes with their functional requirements. Here we review how the metabolic and phenotypic plasticity of macrophages are intrinsically connected with the hypoxia stress sensors and the unfolded protein response in the endoplasmic reticulum, and how these molecular pathways participate in the maladaptive polarization of macrophages in human pathology and chronic inflammation.